Cohomology theories in synthetic differential geometry (1986)
One way of formulating De Rham's theorem' smoothly in parameters' is to construct the De Rham cohomology groups, and the (duals of the) singular homology groups as sheaves of smooth modules over the space of parameters, and then to assert that these sheaves are canonically isomorphic.